Analisis Hasil Belajar Mahasiswa pada Pokok Bahasan Hukum Ohm dan Kirchoff dalam Matakuliah Elektronika Dasar I - Wahyudi Wahyudi (Department of Physics Education, Universitas Mataram, 2015)
The purpose of this description is to analyze the results of student learning physics education in sub subject Ohm's law and Kirchoff laws in subject 1 Basic Electronics and possible solutions, which are expected to minimize the percentage of errors. The author uses quantitative methods to support this description. First of all, I have shared the instruments to students of the third semester. Then from the results obtained, the authors categorize the types of errors, analyze and find the reason of the student errors. Once analyzed, the authors obtain the result that the students' understanding of the application of Ohm's law in category 3, the percentage of the greatest mistakes that 90%, followed by the category 1 by 80% and the lowest category of 2 (20%). Then from the results of the analysis of Kirchoff laws, obtained the largest percentage error in the category of category 3 by 90%, then 40% of category 2 and category 1 by 10%. From the analysis it can be concluded that the ability of students to master the fundamental law of electricity is low.